2021
DOI: 10.1007/s11523-021-00795-5
|View full text |Cite|
|
Sign up to set email alerts
|

Liquid Biopsy for Prognosis and Treatment in Metastatic Colorectal Cancer: Circulating Tumor Cells vs Circulating Tumor DNA

Abstract: Liquid biopsy recently gained widespread attention as a noninvasive alternative/complementary technique to tissue biopsy in patients with cancer. As technological advances have improved both feasibility and turnaround time, liquid biopsy has expanded tumor molecular analysis with acknowledgement of both spatial and temporal heterogeneity, overcoming many limitations of traditional tissue biopsy. Because of its diagnostic, prognostic, and predictive value, liquid biopsy has been extensively studied also in meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 119 publications
0
16
0
Order By: Relevance
“…( 11 , 12 ) High thymidine kinase 1 (TK1) expression level correlated with a larger survival benefit in FTD/TPI treatment, ( 30 ) although no significant difference in TKI expression according to PTL was reported. Moreover, evolving technologies of liquid biopsies using circulating tumor DNA (ctDNA) and circulating tumor cells (CTCs) analysis have accelerated research on the dynamism of clonal evolution, enabling us to reveal molecular profiling, monitor clonal dynamics, and identify resistance mechanism by longitudinal biopsies ( 31 33 ). The subgroup and exploratory biomarker analyses in the CORRECT trial suggested that a survival benefit was observed regardless of RAS or PIK3CA mutational status in ctDNA.…”
Section: Discussionmentioning
confidence: 99%
“…( 11 , 12 ) High thymidine kinase 1 (TK1) expression level correlated with a larger survival benefit in FTD/TPI treatment, ( 30 ) although no significant difference in TKI expression according to PTL was reported. Moreover, evolving technologies of liquid biopsies using circulating tumor DNA (ctDNA) and circulating tumor cells (CTCs) analysis have accelerated research on the dynamism of clonal evolution, enabling us to reveal molecular profiling, monitor clonal dynamics, and identify resistance mechanism by longitudinal biopsies ( 31 33 ). The subgroup and exploratory biomarker analyses in the CORRECT trial suggested that a survival benefit was observed regardless of RAS or PIK3CA mutational status in ctDNA.…”
Section: Discussionmentioning
confidence: 99%
“…59 Furthermore, assessment of ctDNA allows the comprehensive detection of different mutated cancer clones, which may arise in different metastatic sites. 60 In this respect, several NGS extended gene panels for liquid biopsy analysis are currently available.…”
Section: Mutational Landscape Of Metastatic Colorectal Cancermentioning
confidence: 99%
“…A potential advantage of liquid biopsy is the possibility of repeating this procedure to evaluate the dynamic tumor mutation changes under the selective pressure of therapies for a better choice of molecular target drugs to use 59 . Furthermore, assessment of ctDNA allows the comprehensive detection of different mutated cancer clones, which may arise in different metastatic sites 60 . In this respect, several NGS extended gene panels for liquid biopsy analysis are currently available.…”
Section: Mutational Landscape Of Metastatic Colorectal Cancermentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA) is a small fragment of gene released from solid lesions into the circulation system, mainly derived from tumor metabolism, and the genomic information carried by it is highly consistent with tumor tissue [ 3 ]. Relevant studies have pointed out that ctDNA detection can more accurately reflect the epigenetics of tumor-related genes, and then can be used to track the occurrence and development of tumors in the body [ 4 ]. At present, many clinical studies [ 5 , 6 ] have shown that it can be used in the prognostic evaluation of various tumors.…”
Section: Introductionmentioning
confidence: 99%